Electrical power systems - Husain, Ashfaq (New Delhi : CBS Publishers & Distributors Pvt Ltd, 2007)
This book is intented to serve as a textbook for B.E/B.Tech. degree students of Electrical Engineering. It will also serve as a text reference for the students of Diploma in Electrical Engineering. This text is also useful for candidate appearing in AMIE, GATE, UPSC Engineering services and other competitive examinations.
Preface -- Load characteristics -- Supply systems -- Conductors -- Power cables -- Line insulators and supports -- Sag and tension -- Line parameters -- Per unit representation -- Short and medium lines -- Long transmission lines -- General network constants -- Power circle diagrams -- Control of voltage and reactive power -- Load flow analysis -- Economic operation of power systems -- Symmetrical faults -- Symmetrical components -- Unsymmetrical faults -- Power systems stability -- Travelling waves -- Overvoltage protection -- Corona -- High voltage direct current -- System neutral -- Tariffs -- Power factor improvement -- Voltage stability -- Flexible ac transmission systems -- Appendix -- Index.
Includes index.
engineering bookfair2015
(for B.E./B. Tech., AMIE, IETE, GATE, UPSC .Engineering Services)
Keywords: Electric power systems